Induction or adjuvant chemotherapy plus concurrent chemoradiotherapy versus concurrent chemoradiotherapy alone in paediatric nasopharyngeal carcinoma in the IMRT era: A recursive partitioning risk stratification analysis based on EBV DNA. (December 2021) - Liang, Yu-Jing; Wen, Dong-Xiang; Luo, Mei-Juan; Tang, Lin-Quan; Guo, Shan-Shan; Wang, Pan; Chen, Qiu-Yan; Liu, Li-Ting; Mai, Hai-Qiang
Abstract: Purpose: To compare the prognosis and adverse effects of induction or adjuvant chemotherapy (IC or AC) plus concurrent chemoradiotherapy (CCRT) versus CCRT alone in paediatric nasopharyngeal carcinoma (NPC) patients in the intensity-modulated radiotherapy (IMRT) era. Methods and materials: 549 patients diagnosed from 2005 to 2021 were enrolled. Our primary endpoint was progression-free survival (PFS). The recursive partitioning analysis (RPA) was applied to derive a risk stratification system. Kaplan–Meier survival curves were used to assess the cumulative survival rates, and cox analysis was applied to evaluate the relationship between variables and endpoints. Results: The RPA-based risk stratification identified three different risk groups. In the intermediate-risk (stage IVa and EBV<4000 copies/ml) group, patients who received IC followed by CCRT achieved a significantly better 3-year PFS rate than those treated with CCRT alone (87.35% versus 75.89%; P = 0.04). But survival benefit was not obtained from the additional IC or AC in the low-risk (stage II-III and EBV<4000 copies/ml) or high-risk (stage II-IVa and EBV≥4000 copies/ml) group. The most common grade 3 or 4 adverse events in patients treated with CCRT, IC + CCRT, and CCRT + AC were neutropenia (8.1%, 33.0% versus 36.9%, respectively) and leukopenia (14.1%, 26.8% versus 32.3%, respectively) with statistically significant difference. Conclusions: Paediatric NPC patients in the intermediate-risk group treated with IC followed by CCRT had significantly better PFS compared with patients treated with CCRT alone. And the overall incidence of acute adverse events in patients treated with IC or AC plus CCRT was higher than in patients treated with CCRT alone. Highlights: EBV DNA was independently associated with risk stratification in paediatric NPC. Paediatric NPC patients with intermediate-risk could benefit from the additional IC. Overall incidence of AE in paediatrics receiving IC/AC + CCRT was significantly higher.